Beeldhouwkunst Amstelpark 84. - Brouwer, Marianne (Amsterdam : Nederlandse Kring van Beeldhouwers Amsterdam, 1984)
Arend, Lucien den ; de Baat, Wouter ; Bailleux, Cesar ; van Bennekum, Henk ; Bierman, Kees ; van den Bighelaar, Frans ; Buijs, Willem ; Clijsen, Joos ; Devens, Dré ; Dijkers, Ruud ; Evelo, Gert-Jan ; Fens, Huib ; De Fluiter, Adri ; Gerard, Höweler ; Goerres, Nina ; Haak, Jan ; Have, Theo ten ; Heikoop, Govert ; Hey, Ans ; Hey, Hans la ; Horvers, Toine ; Höweler, Gerard ; Isik ; van Kervel, Albert ; Kracht, Yvonne ; Leutscher, Hans ; van der Linde, Fred ; Linden, Lo Van der ; Logister, Rob ; Luik, Hieke ; van Maaren, Clementine ; Maingay, Rob ; Mooij, Olaf ; Müller, Dirk ; Nette, Adriaan ; Peters, Ruudt ; Pieters, Godfried ; Popma, Carola ; Radema, Heleen ; Rietman, Liesbeth ; Ruygrok, Marc ; Schabracq, Alexander ; Schepers, Maarten ; Siepman van den Berg, Eja ; Silawanebessy, Lucas ; Strijk, Roeli ; Swinkels, Ad ; Tax, Lettie ; Teeuwen, Roel ; Verhoeven, Adri ; Verwoerd, Yolande ; Viegers, Annelies ; de Vliet, Harry van ; Vollewens, Rob ; Voogt, Har ; Wagemakers, Theo ; Walraeven, Gerard ; de Weijer, Tine van ; van Wetering, Han ; Wijntjes, Erik ; Willemsma, Ids ; de Wit, Niko ; Wolf-Wubben, Fredy
Beeldhouwkunst Amstelpark 1984, Amstelpark Amsterdam, Zuiderkerk, Amsterdam, 12 mei - 2 september 1984
Nederlands & Engels
boek